Novel causative RYR2 indel variant with exon and intron involvement inducing exon 13 skipping in a family exhibiting catecholaminergic polymorphic ventricular tachycardia - Shin, Ju Hyeon; Park, Taek Kyu; Chang, Sung-A.; Jang, Shin Yi; Huh, June; Seol, Chang Ahn; Park, Kyoung-Jin; Kim, Sung Hoon; Kim, Duk-Kyung; Gwag, Hye Bin; Jang, Mi-Ae (Frontiers in Genetics, 2025)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a genetic disorder marked by exercise or stress-induced arrhythmias that lead to syncope or sudden cardiac death. Mutations of the RYR2 gene can cause either CPVT or calcium release deficiency syndrome, with varying impacts on calcium release in cardiomyocytes. These mutations are predominantly missense variants associated with a gain-of-function mechanism. In this report, we present a novel pathogenic RYR2 indel variant in a family afflicted with CPVT based on comprehensive molecular investigations. The proband was a 15-year-old girl who suffered a cardiac arrest during exercise and exhibited frequent premature ventricular beats on a treadmill test, which was consistent with CPVT. Using next-generation sequencing and Sanger sequencing, a novel RYR2 indel variant, NM_001035.3:c.1006-44_1007delinsATTTTG, was identified. Sanger sequencing confirmed the presence of this variant in her mother, who also showed frequent premature ventricular beats on a treadmill test. Further RNA analysis revealed that this variant caused aberrant splicing, resulting in the skipping of exon 13 (r.1006_1170del), which would disrupt the intramolecular domain interactions. This discovery led to the classification of the variant as a likely pathogenic variant. We identified a novel RYR2 indel variant responsible for CPVT and expanded the mutational spectrum of RYR2-related CPVT, emphasizing the importance of comprehensive genetic approaches for variant classification.